2016
DOI: 10.4103/0378-6323.171650
|View full text |Cite
|
Sign up to set email alerts
|

Immunotherapy using purified protein derivative in the treatment of warts: An open uncontrolled trial

Abstract: Immunotherapy with PPD is helpful in the treatment of cutaneous warts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
80
7
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(95 citation statements)
references
References 0 publications
7
80
7
1
Order By: Relevance
“…24 Follow up for a period of six months after release from treatment showed no recurrences in both the groups, however a similar study showed recurrence in 1.8% of the cases treated with PPD immunotherapy at 6 months after treatment. 12 Despite a small sample size in the present study both intralesional PPD and BCG groups showed good response in the treatment of multiple warts, however PPD was marginally better.…”
Section: Discussioncontrasting
confidence: 59%
See 1 more Smart Citation
“…24 Follow up for a period of six months after release from treatment showed no recurrences in both the groups, however a similar study showed recurrence in 1.8% of the cases treated with PPD immunotherapy at 6 months after treatment. 12 Despite a small sample size in the present study both intralesional PPD and BCG groups showed good response in the treatment of multiple warts, however PPD was marginally better.…”
Section: Discussioncontrasting
confidence: 59%
“…A similar study showed 80%complete clearance in multiple verrucae vulgaris (> 10 warts) and 67% complete resolution in multiple verrucae plana (> 10 warts). 12 The difference of higher resolution in their study can be attributed due to higher quantity of PPD being used as well antigen being injected in each wart. Another study on intralesional tuberculin in 17 patients with warts showed complete clearance in 5 (29%) patients, partial response in 10 (59%) patients, and no response in 2 (12%) patients, similar to our study.…”
Section: Discussionmentioning
confidence: 98%
“…Immunotherapy is efficacious in pediatric and adult patients, particularly in cases of multiple or recalcitrant warts. Studies of Candida antigen, MMR, and PPD provided comparable complete response rates of injected warts, from 39% to 88% for candida, 26.5% to 92% for MMR, and 23.3% to 94.4% for PPD . However, BCG appears to be an inferior treatment choice, with clearance rates limited at 33.3%‐39.7%,…”
Section: Discussionmentioning
confidence: 94%
“…Saoji et al injected 2.5 tuberculin units (TU) of PPD into a maximum of 10 lesions (max 25 TU per session) at 2‐week intervals for 4 sessions. 76% showed complete clearance and side effects included mild pain and redness at the injection site . Kerure et al instead used a dosage of 10 IU (0.1 mL) injected into the largest wart every 2 weeks, until wart resolution or a maximum of six treatments.…”
Section: Resultsmentioning
confidence: 99%
“…Both studies showed low recurrence among patients, but some patients (<30%) experienced flu-like symptoms during treatment [21 -29]. In a study performed by Saoji et al, tuberculin PPD showed a complete response rate of 76% in four treatments with very minimal adverse reactions to the antigen [22]. Myobacterium w vaccine showed complete response rates as high as 89% in a study performed by Gupta et al and 93% in a study performed by Garg and Baveja [23,30].…”
Section: Efficacy Of Intralesional Immunotherapies and Intralesional mentioning
confidence: 97%